KENDALA DAN DAMPAK PANDEMI COVID-19 PADA SEKTOR PARIWISATA DAN PERHOTELAN DI KOTA BANDUNG - Era Purike (Cross-border, 2021)
The decline in tourism numbers after the outbreak of the COVID-19 pandemic has had an impact on the reduction in hotel occupancy rates in Bandung. It was recorded that in 2020 there was a decline of 50% or around 3.2 million tourists. This number is lower than in 2019, which was 7.4 million. Meanwhile, foreign tourists in 2019 were only 350 thousand people. The condition of tourism and hospitality in Bandung is greatly affected by the conditions of global tourism and also Indonesia. The deteriorating situation of global and Indonesian tourism has significantly impacted the tourism and hospitality sector in Bandung. The significant decrease in the number of tourists, both local and foreign has caused the hotel to experience several obstacles. Data collection was carried out through interviews and limited surveys to find out the constraints faced by the hotel. The main obstacle faced by hotels is marketing. The pandemic period, which caused everyone to carry out social restrictions and the decline in the level of the economy, caused several marketing strategies carried out by hotels to not be able to increase revenue (revenue). Therefore, it is necessary to have breakthroughs that the tourism sector must immediately do so that tourism can rise and recover. The decline in tourism numbers after the outbreak of the COVID-19 pandemic has had an impact on the reduction in hotel occupancy rates in Bandung. It was recorded that in 2020 there was a decline of 50% or around 3.2 million tourists. This number is lower than in 2019, which was 7.4 million. Meanwhile, foreign tourists in 2019 were only 350 thousand people. The condition of tourism and hospitality in Bandung is greatly affected by the conditions of global tourism and also Indonesia. The deteriorating situation of global and Indonesian tourism has significantly impacted the tourism and hospitality sector in Bandung. The significant decrease in the number of tourists, both local and foreign has caused the hotel to experience several obstacles. Data collection was carried out through interviews and limited surveys to find out the constraints faced by the hotel. The main obstacle faced by hotels is marketing. The pandemic period, which caused everyone to carry out social restrictions and the decline in the level of the economy, caused several marketing strategies carried out by hotels to not be able to increase revenue (revenue). Therefore, it is necessary to have breakthroughs that the tourism sector must immediately do so that tourism can rise and recover.